Association of high consumption of soy products with the risk of cognitive impairment and major neurocognitive disorders: a systematic review and dose-response meta-analysis - Yu, Jialin; Zeng, Hongmei (Frontiers in Nutrition, 2025)
ObjectiveWhile soy products can potentially affect cognitive function through various mechanisms, the dose-response connection of high soy consumption with major neurocognitive disorder or cognitive impairment remains unclear.MethodsA comprehensive retrieval was performed on PubMed, Embase, Cochrane Library, and Web of Science databases up to September 2024, to identify prospective or cohort studies (without language restrictions) examining the link between high soy consumption and the likelihood of developing major neurocognitive disorder or cognitive impairment. Stata (V15) was employed for data analysis, and a restricted cubic spline (RCS) model was employed for examining the dose-response effect.ResultsSix studies incorporating 68,691 participants were included. Elevated consumption of total soy products was markedly correlated to a reduced likelihood of developing major neurocognitive disorder [odds ratios (OR) = 0.92, 95% confidence intervals (95%CI): 0.84–0.99]. While an association with increased risk of cognitive impairment was observed, it was not statistically significant. The dose-response meta-analysis indicated that a 1-g per day increase in the consumption of soy and natto demonstrated a correlation with an 8 and 14% decrease in the likelihood of developing major neurocognitive disorder, respectively. Subgroup analysis suggested a more pronounced protective effect in individuals not experiencing stroke (OR = 0.66, 95%CI: 0.53–0.82). However, soy consumption showed a paradoxical association with the likelihood of developing cognitive impairment (OR = 1.20, 95%CI: 0.83–1.72). Risk data showed no significant association with cognitive impairment. Dose-response data further explained an inverse relationship between dose and risk of cognitive impairment, with higher doses associated with lower risk.ConclusionElevated consumption of diverse soy products exhibited a linear negative correlation with cognitive decline or major neurocognitive disorder; however, significant heterogeneity remained within both the overall analysis and multiple subgroup analyses.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, CRD42024508555.